Manufacturing strategy and perfomance:A study of the UK engineering industry - Sweeney, Mike T.; Szwejczewski, Marek (Cranfield School of Management, 1995)
This paper details the findings of a search for manufacturing "strategic groups" in the engineering industry, that is a set of firms competing within an industry on the basis of similar combinations of business scope and resource commitments. The research methodology used was to adopt stockturns (excluding work in process), as a measure of manufacturing scope. Manufacturing throughtput efficiency was selected as a measure of production engineering resource commitment. An initial grouping of companies was accomplished by using these two manufacturing performance variables. Comparisons were then made of the manufacturing practices and performances of the firms in the four strategic groups that were formed. The results obtained show statistically differences in the performance of each of the strategic groups formed. They can also serve as benchmarks for the evaluation of manufacturing manangement performance. The proposed manufacturing strategy and performance matrix provides a practical framework for strategic planning.